Bacterial and Fungal Endophytes of Grapevine Cultivars Growing in Primorsky Krai of Russia - Olga A. Aleynova; Nikolay N. Nityagovsky; Alexey A. Ananev; Andrey R. Suprun; Zlata V. Ogneva; Alina A. Dneprovskaya; Alina A. Beresh; Alexandra S. Dubrovina; Pavel A. Chebukin; Konstantin V. Kiselev (Horticulturae, 2023)
In this study, the biodiversity of endophytic bacteria of cultivated grape varieties from the vineyards of Primorsky Krai, Russia, was analyzed for the first time. Far Eastern grape varieties with a high level of stress resistance are a unique object of research as they are cultivated in cold and humid climates with a short summer season. Grapevine endophytic microorganisms are known as promising agents for the biological control of grapevine diseases and agricultural pests. Using genomic approaches, we analyzed the biodiversity of the endophytic bacteria and fungi in the most common grape varieties of Primorsky Krai, Russia: Vitis vinifera × Vitis amurensis cv. Adele (hybrid No. 82-41 F3), Vitis riparia × V. vinifera cv. Mukuzani (pedigree unknown), two cultivars Vitis labrusca × V. riparia cv. Alfa, and Vitis Elmer Swenson 2-7-13 cv. Prairie Star for the first time. The main representatives of the endophytic microorganisms included 16 classes of bacteria and 21 classes of fungi. The endophytic bacterial community was dominated by Gammaproteobacteria (31–59%), followed by Alphaproteobacteria (9–34%) and, to a lesser extent, by the classes Bacteroidia (9–22%) and Actinobacteria (6–19%). The dominant fungal class was Dothideomycetes (43–77%) in all samples analyzed, with the exception of the grapevine cv. Mukuzani from Makarevich, where Malasseziomycetes was the dominant fungal class. In the samples cv. Alfa and cv. Praire Star, the dominant classes were Tremellomycetes and Microbotriomycetes. A comparative analysis of the endophytic communities of the cultivated grape varieties and the wild grape V. amurensis Rupr. was also carried out. We found that 18–20% of the variance between the endophytic communities accounted for the differences between the cultivated and wild grapevines, while the factors “plant location” and “individual plants” accounted for 50–56% and 3–10% of the variance, respectively. The results of this study can be used to develop new means of biocontrol in vineyards to protect plants from abiotic stresses and pathogens.